Senam Yoga untuk Mengurangi Intensitas Nyeri Haid pada Remaja - Izzatun Nida Ulhaq; Tria Puspita Sari (Pusat Riset dan Inovasi Nasional, 2025)
Background : Menstrual pain is caused by an increase in prostaglandin production triggered by a decrease in estrogen and progesterone hormone levels. Among the non-pharmacological approaches that can be used to reduce pain during menstruation is yoga therapy. Objective: The purpose of this literature review is to examine the relationship between yoga exercises and dysmenorrhea in reducing pain intensity among adolescents. The research method used in this literature review study is to obtain from the search for scientific research articles using the google scholar data base. As many as 279 articles were obtained and then identification and screening were carried out, so that 5 random articles were obtained that fit the criteria. The population in all five studies consisted of adolescent girls. Results: The findings from the five studies show that there is a relationship between yoga exercises and dysmenorrhea in reducing pain intensity among adolescents. Conclusion: It is recommended that adolescent girls, especially those who frequently experience dysmenorrhea, practice yoga exercises regularly to minimize the pain level during menstruation.